Diferença no tamanho de cascas de ovos de colônias de Panstrongylus megistus - Rosa, João Aristeu da [UNESP]; Justino, Hernany H G [UNESP]; Barata, José M S (Universidade de São Paulo (USP), Faculdade de Saúde Pública, 2003)
O objetivo do estudo foi avaliar as mensurações de cascas de ovos de duas colônias laboratoriais e uma silvestre de P. megistus. de cada uma das colônias, 50 cascas de ovos foram mensuradas por meio de microscópio estereoscópico e sistema de análise de imagem QWin. A análise estatística foi efetuada utilizando o teste t-Student, não pareado no programa INSTAT. A largura, o comprimento e o diâmetro da abertura opercular das cascas de ovos de uma colônia silvestre foram maiores que de duas colônias laboratoriais de P. megistus.

The objective of the study was to evaluate the measurements of eggshells from three colonies of P. megistus, two from the lab and one from a sylvatic habitat. Fifty eggshells from each colony were measured with the use of a stereoscopic microscope and the Qwin image analysis system,. The statistical analysis was performed using unpaired t-test in INSTAT program. The length, width and diameter of the opercular opening of the eggshells from the sylvatic colony were larger than the two laboratorial colonies of P. megistus.
Differences in the size of eggshells among three Pangstrongylus megistus colonies
Keywords: Panstrongylus; Casca de ovo; Morfometria; Panstrongylus megistus; Panstrongylus; Eggshell; Morphometry; Panstrongylus megistus